An RNA aptamer that interferes with the DNA binding of the HSF transcription activator - Zhao, Xiaoching (Oxford University Press, 2006)
Heat shock factor (HSF) is a conserved and highly potent transcription activator. It is involved in a wide variety of important biological processes including the stress response and specific steps in normal development. Reagents that interfere with HSF function would be useful for both basic studies and practical applications. We selected an RNA aptamer that binds to HSF with high specificity. Deletion analysis defined the minimal binding motif of this aptamer to be two stems and one stem–loop joined by a three-way junction. This RNA aptamer interferes with normal interaction of HSF with its DNA element, which is a key regulatory step for HSF function. The DNA-binding domain plus a flanking linker region on the HSF (DL) is essential for the RNA binding. Additionally, this aptamer inhibits HSF-induced transcription in vitro in the complex milieu of a whole cell extract. In contrast to the previously characterized NF-κB aptamer, the HSF aptamer does not simply mimic DNA binding, but rather binds to HSF in a manner distinct from DNA binding to HSF.